ANALISIS POTENSI DAYA TARIK WISATA BENTENG TIWORO DI KECAMATAN TIWORO KEPULAUAN KABUPATEN MUNA BARAT - Hikma Dani Syamsuddin, Wa Ode; Niampe, La; Syahrun, Syahrun (Jurnal Penelitian Budaya, 2021)
This study aims to determine the potential of Tiworo Fort in Tiworo Islands District, West Muna Regency, analyze its potential in the 4A formulation and analyze the government's efforts in developing the Tiworo Fort site. The theory used to read the data is Tourism Destination Development. The method used is descriptive qualitative method, through observation, interviews and documentation. The results of the research on the analysis of the potential tourist attraction of Tiworo Fort consist of 1) Sangia Barakati Mosque, 2) King's Tombs, and 3) King's Inauguration Stone. While the results of the analysis in the 4A formulation obtained 1) Attraction, namely the Sangia Barakati Mosque, the King's Tombs, and the King's Inauguration Stone. 2) Amenity (facilities), namely lodging business, and supporting infrastructure that can provide services and comfort for tourists covering the fields of Health, Electricity, and Communication Networks. 3) Accessibility (accessibility), including access to land, sea and air routes equipped with road signs, 4) Supporting Services (additional services), namely the presence of the West Muna Regency Tourism Office. Furthermore, related to the government's efforts, it can be seen with the construction of the gate and the plan to restore the mosque to a sleeping formKeywords: Tourist Attraction, Historical Tourism, Fort, Tiworo